Development and Prospects of Triboelectric Nanogenerators in Sports and Physical State Monitoring - Zhang, Jingshui; Yang, Zhou; Liang , Xin (Frontiers in Materials, 2022)
Sports and physical fitness are important parts in people’s daily life. By sticking to exercise we can better enjoy a healthy life . Scientific and accurate monitoring of sports training and individual physical condition is important. However, many challenges still need to be solved, such as the complex design of measurement devices, the external power supplies, inaccurate measurement data, unscientific measurement methods, and so on. Recently, the TENG-based self-powered real-time measurement sensors have been attracted much more attentions due to their unique advantages such as wearable features, simple construction, wide choice of materials and without external power supply. They can measure a wide range of real-time data such as haptics, velocity, pressure and dynamic movement. In addition, they can also be made into a human-machine interactive device to provide athletes with a scientific approach to training. In this review, the working principle of TENG is summarized and clarified. Moreover, the applications of TENG in the areas of tactical strategy in sports, individual sports training and physical state monitoring are also reviewed. Finally, the challenges and development opportunities faced by TENG are also discussed and summarized.